Social Issues Faced by Spinal Cord Injury Patient with Bladder and Bowel Dysfunction – A Cross-Sectional Study - U. Sumiya Begam; P. Thirunavukkarasu; A. Rajakumar; K. Chitrarasu; R. M. Kamakshi; K. Premalatha; A. Guna (Indian Journal of Physical Medicine & Rehabilitation)
Background: The disruption of autonomic function following a spinal cord injury (SCI) is common and can negatively affect quality of life. As social engagement and relationships are critical for well-being and quality of life, it is important to gain a detailed understandings about how bladder and bowel dysfunction impact on social participation. People living with SCI can experience diminished opportunities to socialise and develop relationships because of problems such as a lack of financial and transportation resources, poor environmental accessibility, the negative attitudes of others and depression. Aim: The aim of this study was to determine social issues faced by SCI patients with bladder and bowel dysfunction. Study Design: This was a cross-sectional study. Fifty-five SCI patients with bladder and bowel dysfunction were recruited for this study. Materials and Methods: International SCI survey questionnaires were used and telephonic call interviews were done. Results: Quadriplegic patients faced issues for bowel and bladder management, architectural barriers and psychosocial issues than paraplegic persons. Conclusion: This study emphasize on the importance of health education and psychological counselling to the SCI patients as well as to their family. This study also throws light on the areas where we as a society needs to improve to provide a better environment for the disabled so as to make their lives less troublesome.